Effects of whole body vibration on cardiac autonomic function and exercise capacity in renal transplant recipients. (22nd May 2019) - Maia, Tuíra O; Paiva, Dulciane N; Filho, Dário C Sobral; Cavalcanti, Frederico CB; Rocha, Livia G; Júnior, Aluísio RA Macedo; Marinho, Patrícia Érika de Melo
No abstract available